Self‐Assembly Approach Towards MoS2‐Embedded Hierarchical Porous Carbons for Enhanced Electrocatalytic Hydrogen Evolution. Issue 6 (22nd December 2020) - Liu, Yuping; Wang, Hongxing; Liu, Fengru; Kang, Jialing; Qiu, Feng; Ke, Changchun; Huang, Yu; Han, Sheng; Zhang, Fan; Zhuang, Xiaodong
Abstract: Transition metal‐based nanoparticle‐embedded carbon materials have received increasing attention for constructing next‐generation electrochemical catalysts for energy storage and conversion. However, designing hybrid carbon materials with controllable hierarchical micro/mesoporous structures, excellent dispersion of metal nanoparticles, and multiple heteroatom‐doping remains challenging. Here, a novel pyridinium‐containing ionic hypercrosslinked micellar frameworks (IHMFs) prepared from the core–shell unimicelle of s ‐poly(tert‐butyl acrylate)‐ b ‐poly(4‐bromomethyl) styrene ( s ‐PtBA‐ b ‐PBMS) and linear poly(4‐vinylpyridine) were used as self‐sacrificial templates for confined growth of molybdenum disulfide (MoS2 ) inside cationic IHMFs through electrostatic interaction. After pyrolysis, MoS2 ‐anchored nitrogen‐doped porous carbons possessing tunable hierarchical micro/mesoporous structures and favorable distributions of MoS2 nanoparticles exhibited excellent electrocatalytic activity for hydrogen evolution reaction as well as small Tafel slope of 66.7 mV dec −1, low onset potential, and excellent cycling stability under acidic condition. Crucially, hierarchical micro/mesoporous structure and high surface area could boost their catalytic hydrogen evolution performance. This approach provides a novel route for preparation of micro/mesoporous hybrid carbon materials with confined transition metal nanoparticles for electrochemical energy conversion. Abstract : Reactive micelles : Due to its high stability and unique core–shell structure, unimicelle could be hypercrosslinked into ionic hypercrosslinked micellar frameworks, which were used as a soft template to prepare tunable hierarchical porous carbons with confined MoS2 growth for enhanced hydrogen evolution reaction.